THE RELATIONSHIP OF PUSKESMAS HEAD'S LEADERSHIP STYLE AND WORK MOTIVATION WITH EMPLOYEE JOB SATISFACTION AT UPT PUSKESMAS SUKARAMAI MEDAN YEAR 2024 - Sembiring, Chory Vevayosa Br; Munthe, Seri Asnawati; Dachi, Rahmat Alyakin; Silitonga, Erwin (TOUR HEALTH JOURNAL, 2024)
Background: To determine the relationship between the leadership style of the head of the community health center and the job satisfaction of employees of the Sukaramai Community Health Center Technical Services Unit. Purpose: This research aims to determine the relationship between the leadership style of the head of the Community Health Center and the work motivation of the Sukaramai Community Health Center employees. Method: This type of research is quantitative research with a sample of 34 respondents. The data collection method used in data processing is using a direct questionnaire. The data processing technique uses the Chi Square test. The results of this research show that there is a relationship between leadership style and job satisfaction with a significant value of 0.000 which is smaller than 0.05. The research results also show that there is a relationship between work motivation and job satisfaction with a significant value of 0.000, which is smaller than 0.05. Based on the results of the hypothesis test, there is a significant influence between the leadership style variables on the job satisfaction of the Sukaramai Community Health Center Technical Services Unit employees. Disscusion and Conclusion: The results of the research show that the leadership style of the head of the community health center and work motivation are related to employee job satisfaction in the Sukaramai Community Health Center Technical Services Unit, so it is necessary to improve the quality of leadership through leadership training. Likewise, work motivation requires giving awards, opportunities to increase career levels, providing incentives and other efforts to increase job satisfaction.